2017
DOI: 10.1016/j.yhbeh.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and reproductive effort in male primates

Abstract: Considerable evidence suggests that the steroid hormone testosterone mediates major life-history trade-offs in vertebrates, promoting mating effort at the expense of parenting effort or survival. Observations from a range of wild primates support the “Challenge Hypothesis,” which posits that variation in male testosterone is more closely associated with aggressive mating competition than with reproductive physiology. In both seasonally and non-seasonally breeding species, males increase testosterone production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 311 publications
3
107
1
Order By: Relevance
“…Men's provisioning roles also represent social mechanisms through which they acquire status in the community (Boyette et al, ). Thus, these represent potential psychobiological pathways linking elevated T and provisioning among Bondongo fathers, as risk taking behavior and competition for status are both social–behavioral domains that have been linked to elevated T in humans and other primates (Boyette et al, ; Gray, Reece, et al, ; Muller, ). For fathers' OT, past observational research on Israeli families showed that men with elevated OT were more affectionately and positively engaged when they interacted with their infants (Feldman et al, , ; Gordon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Men's provisioning roles also represent social mechanisms through which they acquire status in the community (Boyette et al, ). Thus, these represent potential psychobiological pathways linking elevated T and provisioning among Bondongo fathers, as risk taking behavior and competition for status are both social–behavioral domains that have been linked to elevated T in humans and other primates (Boyette et al, ; Gray, Reece, et al, ; Muller, ). For fathers' OT, past observational research on Israeli families showed that men with elevated OT were more affectionately and positively engaged when they interacted with their infants (Feldman et al, , ; Gordon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, these trade-offs may bias against helping in species with yearround nesting but not in seasonal species [98]. In the latter, individuals who did not manage to breed will anyway have to wait until the next year to mate, and therefore the reduced testosterone levels associated with helping [96,99] will not compromise mating success in the following year.…”
Section: (A) Hormonal Mechanismsmentioning
confidence: 99%
“…In males, testosterone is required for reproductive processes such as sexual behavior and sperm production (Borst and Yarrow, 2015; Muller, 2016). Outside the reproductive system, testosterone has important actions such as maintaining muscle mass and bone density of men (Borst and Yarrow, 2015; Sinnesael et al, 2011).…”
Section: Phytoandrogensmentioning
confidence: 99%